Analysis of Cash Flow Reports as a Measuring Tool For Financial Performance Effectiveness (Case Study of PT. Astra Agro Lestari Tbk.): Analysis of Cash Flow Reports as a Measuring Tool For Financial Performance Effectiveness (Case Study of PT. Astra Agro Lestari Tbk.) - Erlyna Tri Rohmiatun (Institute of Computer Science (IOCS), 2020)
Corporate performance appraisal reports especially finance need to be done to determine the level of achievement and success of the company in carrying out its activities in order to empower the financial resources available. The type of data obtained from the secondary company data uploaded on the page //http:www.idx.co.id/ and //http:www.astra-agro.co.id/ in the form of financial statements, namely the balance sheet and income statement during the observation period in 2014 to 2018. The data analysis technique used was descriptive analysis technique. Purpose of this research is to know the cash flow analysis in assessing performance at PT. Astra Agro Lestari, Tbk during 2014-2018. Ratio analysis will be used in this study. Among these ratios are the ratio of cash flows (AK), ratio of cash to interest coverage (CKB), cash ratio to current debt (KHL), capital expenditure ratio (PM), ratio of Total Debt (HT). Calculation of ratio to a) years to years b) years to base, c) compared to similar industries. By using the calculation of the ratio method, the results are unfavorable so that it can be concluded that the performance of PT. Astra Agro Lestari Tbk. 2014 until 2018 using the calculation of the above ratio has an underperformance.